Design and Verification of a New Fixture for Machining of Porous Blocks for Medical CAD/CAM Systems - Mario Sokac; Aleksandar Milosevic; Zeljko Santosi; Djordje Vukelic; Igor Budak (Applied Sciences)
This paper presents a new innovative approach for designing and manufacturing a fixture for locating and clamping porous blocks of biocompatible material, which is required for their machining on CNC machines. Manufacturing porous blocks for their application in medical and/or dental fields is gaining traction. However, limited solutions are available today. In order to address this issue, a new design has been proposed for locating and clamping porous blocks. Finite element analysis was used as a verification tool for the designed fixture with the workpiece, which showed a low concentration of stresses. After the manufacturing, dimensional verification in the form of CAD analysis showed small deviations on the manufactured object with deviations peaking around +0.015 mm, thus validating the adequate locating and clamping of the workpiece.